Additive harmful effects of acute kidney injury and acute heart failure on mortality in hospitalized patients - Hyung Eun Son; Jong Joo Moon; Jeong-min Park; Ji Young Ryu; Eunji Baek; Jong Cheol Jeong; Ho Jun Chin; Ki Young Na; Dong-wan Chae; Seung Seok Han; Sejoong Kim (The Korean Society of Nephrology, 2022)
Background Organ crosstalk between the kidney and the heart has been suggested. Acute kidney injury (AKI) and acute heart failure (AHF) are well-known independent risk factors for mortality in hospitalized patients. This study aimed to investigate if these conditions have an additive effect on mortality in hospitalized patients, as this has not been explored in previous studies. Methods We retrospectively reviewed the records of 101,804 hospitalized patients who visited two tertiary hospitals in the Republic of Korea over a period of 5 years. AKI was diagnosed using serum creatinine-based criteria, and AHF was classified using International Classification of Diseases codes within 2 weeks after admission. Patients were divided into four groups according to the two conditions. The primary outcome was all-cause mortality. Results AKI occurred in 6.8% of all patients (n = 6,920) and AHF in 1.2% (n = 1,244). Three hundred thirty-one patients (0.3%) developed both conditions while AKI alone was present in 6,589 patients (6.5%) and AHF alone in 913 patients (0.9%). Among the 5,181 patients (5.1%) who died, 20.8% died within 1 month. The hazard ratio for 1-month mortality was 29.23 in patients with both conditions, 15.00 for AKI only, and 3.39 for AHF only. The relative excess risk of interaction was 11.85 (95% confidence interval, 2.43‒21.27), and was more prominent in patients aged <75 years and those without chronic heart failure. Conclusion AKI and AHF have a detrimental additive effect on short-term mortality in hospitalized patients.